Football Goalkeepers’ Ability in Luwu: Penalty Kick Anticipation (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
One of the techniques which must be mastered by a goalkeeper is to be able to anticipate the direction of the ball. The aim of the research is how much the level of ability of the goalkeeper in anticipating a penalty kick in Luwu Regency. The descriptive method is defined as a method of determining the outcome of a single attribute (variable), not comparing and looking for associations with other variables. The population in this study are goalkeepers in Luwu Regency. The sample in this study are 20 goalkeepers spread across Luwu Regency. The results of this study provide an overview of the level of goalkeepers’ ability in Luwu Regency with an anticipation of a penalty kick of 55%. The conclusion is that the ability level of goalkeepers in Luwu Regency is in the medium category.